How forests attract rain: an examination of a new hypothesis - Sheil, Douglas; Murdiyarso, Daniel (2009)
A new hypothesis suggests that forest cover plays a much greater role in determining rainfall than previously recognized. It explains how forested regions generate large-scale flows in atmospheric water vapor. Under this hypothesis, high rainfall occurs in continental interiors such as the Amazon and Congo river basins only because of near-continuous forest cover from interior to coast. The underlying mechanism emphasizes the role of evaporation and condensation in generating atmospheric pressure differences, and accounts for several phenomena neglected by existing models. It suggests that even localized forest loss can sometimes flip a wet continent to arid conditions. If it survives scrutiny, this hypothesis will transform how we view forest loss, climate change, hydrology, and environmental services. It offers new lines of investigation in macroecology and landscape ecology, hydrology, forest restoration, and paleoclimates. It also provides compelling new motivation for forest conservation